Electrical and thermal transport properties of Pb1−xSnxSe solid solution thermoelectric materials. Issue 19 (21st May 2015) - Wu, Chao-Feng; Wei, Tian-Ran; Li, Jing-Feng
<x xml:space="preserve">Abstract</x> Semiconducting characteristics of Pb1−xSnxSe solid solutions were investigated to reveal the Sn substitution effects on thermoelectric performance.